PIN1 and PIN4 inhibition via parvulin impeders Juglone, PiB, ATRA, 6,7,4′-THIF, KPT6566, and EGCG thwarted hepatitis B virus replication - Saeed, Umar; Piracha, Zahra Zahid (Frontiers in Microbiology, 2023)
Human Parvulin Peptidyl prolyl cis/trans isomerases PIN1 and PIN4 plays important roles in cell cycle progression, DNA binding, protein folding and chromatin remodeling, ribosome biogenesis, and tubulin polymerization. Here, we found that endogenous PIN1 and PIN4 were upregulated in selected hepatocellular carcinoma cell lines. In this study, we inhibited PIN1 and PIN4 via parvulin inhibitors (Juglone, PiB, ATRA, 6,7,4′-THIF, KPT6566, and EGCG). The Native Agarose Gel Electrophoresis (NAGE) immunoblotting analysis revealed that upon PIN1 and/or PIN4 inhibition, the HBc protein expression and core particle or capsid synthesis reduced remarkably. The effects of PIN4 inhibition on HBV replication were more pronounced as compared to that of PIN1. The Northern and Southern Blotting revealed reduced HBV RNA and DNA levels. During HBV course of infection, Juglone, PiB, ATRA, 6,7,4′-THIF, KPT6566, and EGCG mediated inhibition of PIN1 and PIN4 significantly lowered HBV transcriptional activities without affecting total levels of covalently closed circular DNA. Similar to the inhibitory effects of PIN1 and PIN4 on HBV replication, the knockdown of PIN1 and PIN4 in HBV infection cells revealed significantly reduced amounts of intracellular HBc, HBs, HBV pgRNA, SmRNAs, core particles, and HBV DNA synthesis. Likewise, PIN1 and PIN4 KD abrogated extracellular virion release, naked capsid levels, and HBV DNA levels. In comparison to PIN1KD, the PIN4KD showed reduced HBc and/or core particles stabilities, indicating that PIN4 is more critically involved in HBV replication. Chromatin immunoprecipitation assays revealed that in contrast to DNA binding PIN4 proteins, the PIN1 did not show binding onto cccDNA. Similarly, upon PIN1 KD the HBc recruitment to cccDNA remained unaffected. However, PIN4KD significantly abrogated PIN4 binding to cccDNA, consequently HBc recruitment onto cccDNA and restricted HBV transcriptional activities. These effects were more pronounced in PIN4 KD cells upon drug treatment in HBV infected cells. The comparative analysis revealed that in contrast to PIN1, the PIN4 is more critically involved in enhancing HBV replication. Thus, PIN1 and PIN4 inhibition or knockdown might be a novel therapeutic target to suppress HBV infection.